Interactions Between Temperature Variability and Reproductive Physiology Across Traits in an Intertidal Crab - Lam, Emily K.; Abegaz, Metadel; Gunderson, Alex R.; Tsukimura, Brian; Stillman, Jonathon H. (Frontiers in Physiology, 2022)
Thermal extremes alter population processes, which can result in part from temperature-induced movement at different spatial and temporal scales. Thermal thresholds for animal movement likely change based on underlying thermal physiology and life-history stage, a topic that requires greater study. The intertidal porcelain crab Petrolisthes cinctipes currently experiences temperatures that can reach near-lethal levels in the high-intertidal zone at low tide. However, the thermal thresholds that trigger migration to cooler microhabitats, and the extent to which crabs move in response to temperature, remain unknown. Moreover, the influence of reproductive status on these thresholds is rarely investigated. We integrated demographic, molecular, behavioral, and physiological measurements to determine if behavioral thermal limits varied due to reproductive state. Demographic data showed a trend for gravid, egg bearing, crabs to appear more often under rocks in the cooler intertidal zone where crab density is highest. In situ expression of 31 genes related to stress, metabolism, and growth in the field differed significantly based on intertidal elevation, with mid-intertidal crabs expressing the gene for the reproductive yolk protein vitellogenin (vg) earlier in the season. Furthermore, VG protein levels were shown to increase with density for female hemolymph. Testing for temperatures that elicit movement revealed that gravid females engage in heat avoidance behavior at lower temperatures (i.e., have a lower voluntary thermal maximum, VTmax) than non-gravid females. VTmax was positively correlated with the temperature of peak firing rate for distal afferent nerve fibers in the walking leg, a physiological relationship that could correspond to the mechanistic underpinning for temperature dependent movement. The vulnerability of marine organisms to global change is predicated by their ability to utilize and integrate physiological and behavioral strategies in response to temperature to maximize survival and reproduction. Interactions between fine-scale temperature variation and reproductive biology can have important consequences for the ecology of species, and is likely to influence how populations respond to ongoing climate change.